2015
DOI: 10.5137/1019-5149.jtn.10747-14.4
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of neural precursor cells in the treatment for parkinson disease: an efficacy and safety analysis

Abstract: and psychiatric problems. Recent studies demonstrated that transplantation of all kinds of human stem cells into patients with PD could help replacing endogenous degenerating dopamine (DA) neurons and ameliorate the clinical symptoms of PD (2, 6, 7).Recent studies have revealed the successful reversal of parkinsonian symptoms in monkeys, rats, and patients with PD after transplantation of different kinds of stem cells (18,22,23,24). However, the safety and valuation of transplantation of neural precursor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Up to date, there are 108 registered clinical trials on MSCs (http://www.clinicaltrials.gov), all of which are based on their neuroprotective effects (Ng et al, ). Apart from MSCs, human neural stem cells have also been used to treat patients with Parkinson disease, traumatic spinal cord injury, and chronic ischaemic stroke based on the cell replacement therapy (Kalladka, Sinden, Pollock, et al, ; Lige & Zengmin, ; Shin, Kim, Yoo, et al, ). Yet, adult stem cell‐derived neural cells have not been attempted for the cell replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, there are 108 registered clinical trials on MSCs (http://www.clinicaltrials.gov), all of which are based on their neuroprotective effects (Ng et al, ). Apart from MSCs, human neural stem cells have also been used to treat patients with Parkinson disease, traumatic spinal cord injury, and chronic ischaemic stroke based on the cell replacement therapy (Kalladka, Sinden, Pollock, et al, ; Lige & Zengmin, ; Shin, Kim, Yoo, et al, ). Yet, adult stem cell‐derived neural cells have not been attempted for the cell replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were no graft-induced or delivery-related adverse effects. 13 While this particular study seemed to indicate transplantation success, other studies have shown variable outcomes. Most studies have reported that patients experienced moderate improvement, while others have described less well tolerated transplantation procedures.…”
Section: Potential Stem Cell Treatment Options Neural Stem Cellsmentioning
confidence: 68%
“…12 While this study provided proof of principle, human clinical trials remain invaluable when evaluating the safety of new treatment options. A study by Lige et al 13 examined the potential adverse effects of NSC transplantation into patients diagnosed as having PD. The study used NSCs derived from embryonic stem cells to transplant into the patients, ranging from 42 to 79 years of age.…”
Section: Potential Stem Cell Treatment Options Neural Stem Cellsmentioning
confidence: 99%
“… 55 , 56 As Lmx1a contributes to NSC differentiation into dopamine neurons, the transplantation of Lmx1a -overexpressing iNSCs markedly enhances the efficiency of dopamine neuron production and elicits therapeutic effects in a PD mouse model. 57 Although NSC transplantation in PD animal models has shown a certain degree of benefit, 58 , 59 , 60 , 61 additional studies are required to elucidate its clinical efficacy and safety. To date, one report has verified that human parthenogenetic stem cell-derived NSCs (hpNSCs) can successfully engraft, survive long-term and increase dopamine levels in the brains of rodent and nonhuman primate models of PD.…”
Section: Progress In Nsc Transplantation For the Treatment Of Diseasementioning
confidence: 99%